PENGARUH KENDARAAN PARKIR DI EXIT LANEA TERHADAP ARUS JENUH PERSIMPANGAN BERSINYAL - Mashuri
The objective of this study is to identify the effect of a parked vehicle in the exit-lane on saturation flow and intersection evacuation time.Data of 'saturation flow and evacuation time were collected with a survey for several parking distances to stop-line. The research comprised several parking positions in the exit-lane at 21,5m; 31,5m; 41,5m and 51,5m to stop-line respectively and without any parked vehicle. Data was collected during the peak hours on Mardi 140', 15th, 19`h, 20th and 21th 2001, i.e, at 07.00- 11.00 and 13.00- 16.00 WITA. The number of saturated cycles obtained for each condition are 62, 62, 66, 60 and 57 respectively. The number of cycles with a minimum queue length of 50m is 33 for each condition, and these were analysed further. The effect of a parked vehicle is noticed only when the queue length is at least 50m. Saturation flow was determined by Timeslice method of 5 seconds . Data of intersection evacuation time was calculated as a time taken by the latest vehicle leaving from stop-line to the conflict point. The results of this study indicate that the relationship between saturation flow and parking distance followed the Logaritmic model, Y= 73.6,03 ,n(X)+323,53. The relationship between parking distance and evacuation time followed the Eksponential model, Y= 6,1316e-0 0i6 The parked. vehicle at 21,5m caused a reduction of saturation flow of 28%, at 31,5m 19%, at 41,5m 15%, at 51,5m 10%. For the intersection evacuation time found that without any parked vehicle, intersection evac iati0h time is 1,7second. This implies that, 2 second in real on study location still enough for intersection evacuation. The parking distance where the saturation flow has not been influenced by parking vehicle is 82m; for evacuation time is 71m. The comparison of saturation flow for right turn movement to saturation flow for straight ahead movement gives a right turn factor of 0,93